The Relationship Between ABO And Rh Blood Groups With Alopecia Areata - Farzaneh Shirazi; Safoura Shakoei; Maryam Nasimi; Zahra Saffarian; Robabeh Abedini (Mattioli1885, 2023)
Introduction: Alopecia areata (AA) is a common non-scaring hair loss disease. Genetic susceptibility and environmental factors can develop the disease. Objectives: We investigated the association between AA and ABO and Rh blood groups. Methods: This cross-sectional study was done on 200 patients with AA and 200 healthy controls (HCs) between March 2021 and September 2021. Results: The prevalence of blood groups O, A, B, and AB in patients with AA was 30%, 30.5%, 10.5%, and 29%, respectively. A significant difference was detected between the two groups in the frequency of the ABO and ABO*Rh blood groups (p-value < 0.05). Compared to the HCs, the prevalence of the AB and AB+ blood group was higher in AA patients. No significant relationship was detected between sex, BMI, duration of disease, age at onset, severity of alopecia tool (SALT) score, hair loss pattern, and nail involvement with ABO and Rh blood groups (p-value > 0.05). Conclusion: In conclusion, the highest difference was related to the AB+ blood group, so compared to HCs, the AB+ blood group frequency was higher in patients with AA. However, more studies with larger sample sizes on different ethnicities should be performed to verify the results of this study.